The economics of firm productivity : concepts, tools and evidence - Altomonte, Carlo; Di Mauro, Filippo (Cambridge : Cambridge University Press, 2022)
Productivity varies widely between industries and countries, but even more so across individual firms within the same sectors. The challenge for governments is to strike the right balance between policies designed to increase overall productivity and policies designed to promote the reallocation of resources towards firms that could use them more effectively. The aim of this book is to provide the empirical evidence necessary in order to strike this policy balance. The authors do so by using a micro-aggregated dataset for 20 EU economies produced by CompNet, the Competitiveness Research Network, established some 10 years ago among major European institutions and a number of EU productivity boards, National Central Banks, National Statistical institutes, as well as academic Institutions. They call for pan-EU initiatives involving statistical offices and scholars to achieve a truly complete EU market for firm-level information on which to build solidly founded economic policies.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Industrial productivity; Industrial management; Organizational change; International finance